POLA INTERAKSI KEBERAGAMAAN MASYARAKAT MULTIKULTUR DI DESA PENGASTULAN KECAMATAN SERIRIT (Perspektif Pendidikan Sosiokultural) - Gata, I Wayan (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
Pengastulan village has long been known for its people with many Muslims or Islam, but the village in general live in harmony and peace with no significant conflicts. Meanwhile, the origin of the population is also diverse, such as the Balinese, Javanese, Madurese and Bugis tribes, so from this diversity it is certainly very difficult to equate the society customs and regulations. In order to gain valid and reliable data, this research uses qualitative research methods. For logistical data, this article performs several stages of data sorting; 1). Reducing data, 2). Display data, 3). Verify data and, 4). Interpret article data. Related references strongly support the validity of a scientific work, therefore library techniques are also used through literature exploration on scholar google. The results of this study are: how interactions take place in the Pengastulan village community; what efforts are put in the interaction in Pengastulan village, as well as challenges faced in the interaction. The challenges found in the interaction are lack of education, different economic levels and environmental adaptation